Do family and maternal background matter? A multilevel approach to modelling mental health status of Australian youth using longitudinal data - Hashmi, Rubayyat; Alam, Khorshed; Gow, Jeff; March, Sonja (My University, 2022)
Most previous research place great importance on the influence of family and maternal background on child and adolescents' mental health. However, age of onset studies indicates that the majority of the mental health disease prevalence occurs during the youth years. This study investigates the relationship of family and maternal background, as well as individual circumstance on youth mental health status. Data from 975 participants and 4632 observations of aged cohort 15 to 19 years in the Household, Income and Labour Dynamics in Australia (HILDA) longitudinal study were followed for 10 years (2007-2017). Multilevel logistic regression models were used to analyse the impact of youth circumstances on mental health status. The findings suggests that not all dimensions of family and maternal background (especially maternal education) have impacts on youth mental health. We found low household income (AOR: 1.572, 95% CI: 1.017-2.43) and adverse living arrangement (AOR: 1.586, 95% CI: 1.097-2.294) significantly increases mental disorder odds whereas maternal education or occupation fixed effects were not significant. Individual level circumstances have much stronger impact on youth mental health. We found financial shock (AOR: 1.412, 95% CI: 1.277-1.561), life event shock (AOR: 1.157, 95% CI: 1.01-1.326), long term health conditions (AOR: 2.855, 95% CI: 2.042-3.99), smoking (AOR: 1.676, 95% CI: 1.162-2.416), drinking (AOR: 1.649, 95% CI: 1.286-2.114) and being female (AOR: 2.021, 95% CI: 1.431-2.851) have significant deteriorating effects on youth mental health. Our finding is in contrast to the majority of studies in the literature which give a preeminent role to maternal characteristics in child and youth mental health status. Mental health interventions should consider heterogeneity of adverse youth circumstances and health-related behaviours.
PLoS one
Keywords: Adolescents and youth; Childhood and child development; Families and relationships; Health and wellbeing